Radiation Augments the Local Anti-Tumor Effect of In Situ Vaccine With CpG-Oligodeoxynucleotides and Anti-OX40 in Immunologically Cold Tumor Models - Alexander A. Pieper (Frontiers Media S.A., 2021)
IntroductionCombining CpG oligodeoxynucleotides with anti-OX40 agonist antibody (CpG+OX40) is able to generate an effective in situ vaccine in some tumor models, including the A20 lymphoma model. Immunologically “cold” tumors, which are typically less responsive to immunotherapy, are characterized by few tumor infiltrating lymphocytes (TILs), low mutation burden, and limited neoantigen expression. Radiation therapy (RT) can change the tumor microenvironment (TME) of an immunologically “cold” tumor. This study investigated the effect of combining RT with the in situ vaccine CpG+OX40 in immunologically “cold” tumor models.MethodsMice bearing flank tumors (A20 lymphoma, B78 melanoma or 4T1 breast cancer) were treated with combinations of local RT, CpG, and/or OX40, and response to treatment was monitored. Flow cytometry and quantitative polymerase chain reaction (qPCR) experiments were conducted to study differences in the TME, secondary lymphoid organs, and immune activation after treatment.ResultsAn in situ vaccine regimen of CpG+OX40, which was effective in the A20 model, did not significantly improve tumor response or survival in the “cold” B78 and 4T1 models, as tested here. In both models, treatment with RT prior to CpG+OX40 enabled a local response to this in situ vaccine, significantly improving the anti-tumor response and survival compared to RT alone or CpG+OX40 alone. RT increased OX40 expression on tumor infiltrating CD4+ non-regulatory T cells. RT+CpG+OX40 increased the ratio of tumor-infiltrating effector T cells to T regulatory cells and significantly increased CD4+ and CD8+ T cell activation in the tumor draining lymph node (TDLN) and spleen.ConclusionRT significantly improves the local anti-tumor effect of the in situ vaccine CpG+OX40 in immunologically “cold”, solid, murine tumor models where RT or CpG+OX40 alone fail to stimulate tumor regression.